2012
DOI: 10.1371/journal.pone.0047540
|View full text |Cite
|
Sign up to set email alerts
|

Mortality, Severe Acute Respiratory Infection, and Influenza-Like Illness Associated with Influenza A(H1N1)pdm09 in Argentina, 2009

Abstract: IntroductionWhile there is much information about the burden of influenza A(H1N1)pdm09 in North America, little data exist on its burden in South America.MethodsDuring April to December 2009, we actively searched for persons with severe acute respiratory infection and influenza-like illness (ILI) in three sentinel cities. A proportion of case-patients provided swabs for influenza testing. We estimated the number of case-patients that would have tested positive for influenza by multiplying the number of unteste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 12 publications
1
12
0
2
Order By: Relevance
“…6,7,17,18 Our findings are similar to those of other studies in Argentina and the Americas and may underscore the value of collecting standardized virology and epidemiology surveillance data. 1,12 For example, our mortality rates are similar to those estimated in Argentina during 1992-1999, 6,7 in neighboring Brazil, 19 and in the United States. 1 Our influenza-associated hospitalization rates during the pandemic are similar to those estimated using a multiplier model from three sentinel cities in Argentina (2.4 (95% CI 2.0-2.8) per 10 000 person-year).…”
Section: Discussionsupporting
confidence: 76%
“…6,7,17,18 Our findings are similar to those of other studies in Argentina and the Americas and may underscore the value of collecting standardized virology and epidemiology surveillance data. 1,12 For example, our mortality rates are similar to those estimated in Argentina during 1992-1999, 6,7 in neighboring Brazil, 19 and in the United States. 1 Our influenza-associated hospitalization rates during the pandemic are similar to those estimated using a multiplier model from three sentinel cities in Argentina (2.4 (95% CI 2.0-2.8) per 10 000 person-year).…”
Section: Discussionsupporting
confidence: 76%
“…During the 2009H1N1 pandemic in Argentina, it was estimated that the mortality rate per 100,000 person-years (py) ranged from 1.5 among persons aged 5-44 years to 5.6 among persons aged ≥65 years [26]. An analysis of 332 case fatalities infected with A(H1N1)pdm09 virus showed that twenty (6%) were among pregnant or postpartum women of whom only 47% had been diagnosed with comorbid disorders [27].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has demonstrated that the number of obese persons who were hospitalized with complications of the influenza A/H1N1 infection in 2009 was greater than the number of persons of healthy weight [19]. Moreover, obese individuals had a higher death rate and a greater risk of complications following influenza A infections including A/H1N1 virus infection [2325]. …”
Section: Introductionmentioning
confidence: 99%